Vaccine vial stopper performance for fractional dose delivery of vaccines. Issue 7 (3rd July 2017) - Jarrahian, Courtney; Myers, Daniel; Creelman, Ben; Saxon, Eugene; Zehrung, Darin
ABSTRACT: Shortages of vaccines such as inactivated poliovirus and yellow fever vaccines have been addressed by administering reduced—or fractional—doses, as recommended by the World Health Organization Strategic Advisory Group of Experts on Immunization, to expand population coverage in countries at risk. We evaluated 3 kinds of vaccine vial stoppers to assess their performance after increased piercing from repeated withdrawal of doses needed when using fractional doses (0.1 mL) from presentations intended for full-dose (0.5 mL) delivery. Self-sealing capacity and fragmentation of the stopper were assessed via modified versions of international standard protocols. All stoppers maintained self-sealing capacity after 100 punctures. The damage to stoppers measured as the fragmentation rate was within the target of ≤ 10% of punctures resulting in a fragment after as many as 50 punctures. We concluded that stopper failure is not likely to be a concern if existing vaccine vials containing up to 10 regular doses are used up to 50 times for fractional dose delivery.